Indo - Pacific fishery commission (IPFC) : (FAO, 1994)
The papers are related to three topics: employment, labour productivity and income in small-scale fisheries, improved approaches to employment-oriented fisheries management policies, and integration of coastal fisheries management into coastal area management plan.